Legal Compliance of Indonesian Marriage Law with the Universal Declaration of Human Rights - Kennedy, Alexander (Universitas Pelita Harapan, 2025)
The Indonesian Marriage Law Number 1 of 1974 requires marriages to follow the religious laws of both parties, creating challenges for couples from different faiths. These legal constraints often complicate marriage registration, affecting the legal status, inheritance rights, and recognition of children from such unions. The tension between individual rights and religious conformity results in a legal paradox, as Indonesia seeks to balance constitutional freedoms with religious harmony. This article explores the complexities of interfaith marriage in Indonesia, focusing on the interplay between religious doctrines, legal frameworks, and societal attitudes. Using a normative juridical approach, this study analyzes statutory regulations, court decisions, and legal literature to assess the alignment of Indonesia’s laws with international human rights standards, especially Article 16 of the Universal Declaration of Human Rights (UDHR). Case studies show that while some court rulings have supported interfaith marriage, broader legal reforms and social acceptance remain necessary. The article concludes with recommendations for reform, emphasizing the need for legal provisions to accommodate interfaith unions, foster social acceptance, and create a balanced framework that respects religious values and individual freedoms. By promoting open dialogue and a more inclusive legal environment, Indonesia can navigate the complexities of interfaith marriage, balancing tradition with modernity. These efforts could contribute to a society that respects diversity and the evolving aspirations of its people.